The Impact of Creative Accounting Practices on the Reliability of Financial Statements : Applied Research in the National General Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The study aims to highlighting the Creative Accounting practices, identifying  their impact on non reliability of financial statement of Insurance companies and Iraqi Public Reinsurance Company. Certain executive managements resort to creative accounting to falsely portray a better image to financial statement users by means of a set of techniques and mechanisms. Thus, impacting the company activities, The study was carried out in state insurance companies and Iraqi Public Reinsurance Company. Miller model is adopted to measure earning management practices. It is one of the tools to detect creative accounting practices and to measure reliability of accounting information of financial statements by applying  “White” scale on the companies ,sample of the study, The study  has drawn a set of conclusions  most important of which are :all the companies ,sample of the study ,have resorted to creative accounting in their issued financial statements .The purpose behind  is either to maximize their earnings to create a positive effect  on company reputation in the market and  increase incentives and financial rewards or minimize  earnings to reduce their due taxes. In both cases, this is considered manipulation of financial statements. It seems that practicing creative accounting has.